(untitled) (Journal of the Management Sciences, 2025)
Academic staff of universities are supposed to be role models to students and the society at large, hence, they are expected to exhibit positively inclined behaviours. However, reverse is the case as there are many cases of academic staff`s engagement in various forms of deviant behaviours. Job burnout has been identified as the main trigger of workplace deviant behaviour among academic staff especially in Kaduna State University (KASU). Consequently, the current study emerges to examine the effect of the dimensions of job burnout on workplace deviant behaviour among the academic staff of KASU. The study drawing from stressor-emotion model, draws a total of 395 academic staff of the university through stratified sampling design and data were collected through the administration of questionnaire. PLS-SEM was used to test the hypotheses developed for the study at 5% significance level. The findings of the study revealed that emotional exhaustion has an insignificant effect on workplace deviance while depersonalization and reduced personal accomplishment were found to have a positive significant effect on workplace deviant behaviour. The study recommends among others that the university management should sustain its well-being program to suppress the chances of academic staff exposure to emotional exhaustion, provide recognition and reward programmes, and finally, the university management should provide staff`s access to research grants and resources that will boost their feelings of personal accomplishment. The study contributes to theory by examining the multidimensional perspective of job burnout on workplace deviance. On the practical perspective, the findings provide warning to the management of the university to take steps aimed at reducing job burnout so that the negative consequences of WDB are suppressed. The study concludes that the engagement of workplace deviant behaviour among academic staff in KASU is triggered by job burnout.